Pengaruh Ketimpangan Ekonomi, Tingkat Kemiskinan, Tingkat Pendidikan dan Tingkat Pengangguran Terbuka Terhadap Kriminalitas di Indonesia Tahun 2013-2023 - Nadya Soraya; Muhammad Azkia Nurfikr; Ariq Rafi; Muhammad Kurniawan (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Crime cases are a common problem for many countries around the world. It doesn't matter whether the country is a developed country, a developing country or a poor country. In Indonesia itself, there are still many cases of crime, many of which are caused by economic problems such as income inequality, poverty, high levels of unemployment, and low levels of education which can influence crime itself. By knowing whether these economic problem variables influence crime or not, the crime problem in Indonesia can be addressed better. This type of research is included in quantitative research. In this research, we will examine economic inequality, poverty levels, education levels and unemployment rates on crime in Indonesia in 2013-2023. The data used in this research is secondary data, namely data obtained from a second source during the period 2013 to 2023. The type of data used in this research is time series data. The data in this research were obtained from publications from the Indonesian Central Statistics Agency. The data collection method uses the documentation method, namely the method of collecting data on economic inequality, poverty levels, education levels, unemployment and crime rates which is carried out by taking data from various documentation or publications from the Central Statistics Agency (BPS). The research results obtained were that economic inequality had an insignificant positive effect on the crime rate, while the level of education, poverty level and open unemployment rate had an insignificant negative effect on the crime rate.